KEKERASAN SIMBOLIK PADA HARIAN RADAR SULTENG - Pujiningtyas, Arum (BAHASANTODEA, 2015)
Abstract The research problems were (1) how was the symbolic form of violence used in Radar Sulteng Daily? (2) how the mechanisms of symbolic violence used in Radar Sulteng Daily? This research aimed to (1) describe the form of symbolic violence used in Radar Sulteng Daily, and (2) describe the mechanism of symbolic violence used in the Radar Sulteng Daily. The significance of this research were (1) to be a reference material for journalists in increasing the knowledge of science journalism field, especially in using words to be applied in media texts; (2) to increase the students' knowledge in linguistic especially teh studies of media texts analysis. This research used a qualitative method. Data collection methods refered to listening methods of noted technique through several stages, namely reading, observing and marking data by number. Subsequently, the collected data would be classified based on the forms and mechanisms of symbolic violence in order to be easier of analysis data processing. The analysis data using data reduction techniques of Miles and Huberman. Based on the research results, found ten sources of data from three newspapers, Harian Radar Sulteng, Kompas and Media Indonesia. The next ten sources of data were obtained from the obtained sixteen news headlines, political news, crime, business, and law. Furthermore, the sixteen data found six forms of symbolic violence that consisted of blurring (eight data), a bias (two data), and a bias logic (six data). Symbolic vilence mechanism also comprised a sensor mechanism (four data), smoothing (seven data), logical information (four data) and positive information (one data). Keywords: symbolic violence, form, mechanism